Holistic Approaches to Oral Health - A Review - Meena, Komal; Vardhan, Prabhakar; Pamnani, Gulab Chand; Bhatnagar, Sharad (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Globally, oral disorders persist as a significant health concern. A person’s whole quality of life, which goes beyond the capabilities of the craniofacial complex, is closely linked to their oral health. The prevention of periodontal disease and the treatment of other oral disorders have not yielded great results for mainstream Western medicine. Aim and Objective: The aim and objective of the study are to evaluate the role of holistic approach to oral health. Materials and Methods: Different classical Ayurveda texts, websites, journals, and research articles were referred in above context. Results and Discussion: As a result, the hunt for substitute products never ends, and natural phytochemicals that have been extracted from plants and utilized in conventional medicine are seen to be good substitutes for artificial compounds. Several hundred to several thousand years of use have demonstrated the safety and efficacy of the botanicals found in Ayurveda material medica as well as Kriya Kalpa procedures such as Kavala, Gandush, and Pratisarana. Novel preventive or therapeutic approaches for oral health may result from research into the use of botanicals in traditional medicine. Conclusion: It can be concluded that ayurveda and contemporary system of medicine have significant impact in the prevention and management of oral health.